PENENTUAN JENIS KERUSAKAN JALAN DENGAN METODE VISUAL DAN IRI (STUDI KASUS:JALAN RAYA TROSOBO KM 22 – 36, KECAMATAN TAMAN) - ANDINI RIZKI FEBRIANA; Ronny Durrotun Nasihien (NAROTAMA JURNAL TEKNIK SIPIL, 2018)
The availability of actual information on road damage is needed to determine the condition of a road either to monitor road conditions or to improve planning. Information that has been there will be compiled into an information system. Road damage information system created using Geographic Information System (GIS). This modeling using the Google Earth satellite imagery software, the utilization of Microsoft Office 2007, Google Map to describe and process data obtained directly from the survey of the coordinates of the road segment to be constructed as a Information systems. GIS modeling can display road information that informs the road damage condition. It is expected that with the final project of Road Damage Modeling, Based on Geographic Information System (GIS) at Balai Besar Pelaksanaan Jalan nasional VIII, this can assist / facilitate clarification, type and category of road damage.